Audiometric Profile of Patients on Treatment for Drug-Resistant Pulmonary Tuberculosis in Owerri, South-East Nigeria. - Nduagu, Samuel Uchechukwu; Onyeagwara, Ngozi Carol (British Journal of Healthcare and Medical Research, 2023)
Background: Tuberculosis is an existential medical challenge in certain parts of the world necessitating global efforts. Perhaps more challenging is the treatment of drug-resistant forms of the disease as this requires use of second line drugs, predominantly potentially ototoxic aminoglycosides. The hearing impairment so caused, besides constituting social disability, can impair compliance and have far-reaching consequences. This study aimed at assessing the hearing patterns of patients on treatment for drug-resistant pulmonary tuberculosis to determine if, and to what extent their treatment affected their hearing status. Patients and method: The study was an 18-month prospective analysis of consecutive newly diagnosed drug-resistant pulmonary tuberculosis patients in a tertiary hospital in Owerri, Nigeria. Baseline audiometry was conducted on the patients with subsequent monthly audiometry for 3 months during treatment. A control group drawn from normal population and matched for age and sex with the study group was recruited and audiometry performed on the participants in similar pattern. The audiometric patterns of both groups were analyzed and compared using Statistical Package for Social Sciences (SPSS) version 20.0 software for Windows. Statistical significance was set at p< 0.05. Results: Thirty-eight (38) patients treated for drug-resistant pulmonary tuberculosis completed the study alongside thirty-eight (38) control subjects with M:F ratio was 1.53:1. The baseline prevalence of hearing impairment of any sort was 73.7% and 68.4% among the test and control groups respectively, whereas after three months it was 89.5% and 68.4% respectively. The cumulative incidence of hearing loss over three months was 15.8% and 0% respectively. This difference was statistically significant. Conclusion: Treatment of drug-resistant tuberculosis with second line drugs can lead to significant hearing impairment within the first three months of treatment.